ANALISIS PERMASALAHAN RENDAHNYA KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SDN 198/I PASAR BARU - Gisella Amelia Putri; Febrian; Irfan Maulana; Kurnia Nurmadani (Jurnal Tunas Pendidikan, 2025)
This research aims to analyze the problem of low learning activity of students in science and science subjects in class V of SD Negeri 198/I Pasar Baru. The research method used in this research is a qualitative approach. The data sources in this research are the homeroom teacher of class V at SD Negeri 198/I Pasar Baru and students V at SD Negeri 198/I Pasar Baru. Data collection techniques in this research used observation, interviews and document study techniques. The data analysis technique in this research uses the Miles and Huberman model, namely data collection, data reduction, data presentation, as well as drawing conclusions and verification. The research procedure is carried out in three stages, namely the preparation stage, the implementation stage, and the completion and report preparation stage. The results of the research show that in class V of SD Negeri 198/I Pasar Baru there are several learning problems, such as: Low interest in learning from students in science subjects, low learning activity of students, and low interest in reading from students in science subjects. Through this research, it is hoped that it can become a benchmark for educators so that they can improve learning in the future, so that learning can be carried out better.